THE EFFECT OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND SOCIO DEMOGRAPHIC OF AGE ON ENTREPRENEUR INVESTMENT DECISION MAKING - Santosa, R.Ery Wibowo Agung; Khatik, Nur; Muthaher, Osmad (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
The purpose of this research is to investigate the effect of financial literacy level, financial technology and age socio-demographic factors on the investment decision behavior of entrepreneurs. The research respondents were entrepreneurs in Semarang with a sample of 50 people. The sampling technique used in this study is non-probability sampling with a convenience sampling approach. The data were analyzed using the Path Analysis technique. The results of this study indicate that the level of financial literacy and age have a positive effect on the investment decisions of individual entrepreneurs, while financial technology has no significant effect on their decision-making behavior. The practical implication that can be given from the findings of this research is that this study can be used as a basic model for providing information and outreach regarding financial literacy, financial technology and investment decisions by financial institutions and entrepreneurs. Based on the results of statistical data, the financial literacy variable has the greatest influence in determining individual investment decision behavior compared to age socio demographic factors. This explains that a person's knowledge of managing his personal finances is a major factor in determining an investment decision.